Participative decision making and employees job satisfaction: A comparison between public and private pharmaceutical companies in Egypt - Azab, Amal Saadeldeen Elsayed Ali (AUC Knowledge Fountain, 2016)
The study investigated how does participative decision making affect employees' job satisfaction in a specific work setting (Public and private pharmaceutical companies in Egypt). A public pharmaceutical company was chosen as an example for public business sector companies in Egypt, and a comparison was made between the forms of management system applied in the public versus the private sampled companies. The study used in-depth semi- structured interviews with a total number of 32 employees and managers interviewed from the two companies. Results of the study highlighted a strong relation proving that applying participative decision making in the company increases employees’ job satisfaction. In addition, the study assessed four employee-based factors affecting participative decision making and concluded that employee’s efficiency has a positive effect on incorporating the employee in the decision making process, then comes the second factor which is the years of employee’s experience in the same field. On the other hand the study failed to find a strong correlation between the other two factors - the educational level and the managerial level- and participative decision making, suggesting the need for further study. The comparison held in the study included the pathways each company gives for its employees to communicate with the middle and top management levels. It also included four institutional-based factors affecting employees’ satisfaction and participation in decision making; the incentives system, promotion system, concept of hard work in the organizational culture, and disciplinary system and accountability distribution. And the study concluded that the management system applied in the private company encourages employees more to participate in the decision-making process and their incentives system, promotion system, and disciplinary systems were found more satisfying to employees compared to the systems applied in the public company. The study came up with recommendations directed to the management of the public company in order to increase employees’ satisfaction and thereby increase company competitiveness against the fast growing private sector in Egypt.